Definition of Mechanical Indicators of Plastic Details of the Oil-Field Equipment (International Journal of Innovative Research in Computer Science & Technology, 2020)
The analysis of the manufacture of plastic  details of the oil-field equipment was made, which made it  possible to establish the regularity of the shrinkage change  of plastic details from the regimes of their production.  Changes of quality of ready details depending on casting  pressure are defined, and the regularity of the change in  shrinkage, density, ruggedness, hardness, breaking stress at  distension from regimes of casting is established.
Keywords: Manufacturing process; Oil-field equipment, Optimal pressure; Press form, Technological parameters